ON CERTAIN CLASSES OF P-VALENT FUNCTIONS DEFINED BY MULTIPLIER TRANSFORMATION AND DIFFERENTIAL OPERATOR - A. Tehranchi; S. R. Kulkarni; G. Murugusundaramoorthy (Journal of the Indonesian Mathematical Society, 2007)
" PDF File" DOI : http://dx.doi.org/10.22342/jims.13.1.72.27-38